2021
DOI: 10.1108/ijot-05-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of engagement in community based creative activities as an occupation for older adults

Abstract: Purpose The purpose of this study was to explore the experiences of older adults (aged 60 and over) participating in community-based creative arts. With an ever increasing ageing population, understanding the benefits of leisure occupations such as community creative arts will be vital for Occupational Therapists in facilitating participation and active engagement. Design/methodology/approach An empirical qualitative research design with an interpretive phenomenological approach was undertaken. A purposive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Older adults wished for a career, so each occupation depended on their ability to perform daily tasks, such as taking care of plants at home and involving the community in planning career promotion for older adults. Edwards and Owen-Booth (2021) found that occupations for older adults explored community involvement in career promotion through creative activities, showing that older adults had the opportunity to choose a career and an environment arranged to facilitate the occupation.…”
Section: Creation Of Job Opportunities For Older Adultsmentioning
confidence: 99%
“…Older adults wished for a career, so each occupation depended on their ability to perform daily tasks, such as taking care of plants at home and involving the community in planning career promotion for older adults. Edwards and Owen-Booth (2021) found that occupations for older adults explored community involvement in career promotion through creative activities, showing that older adults had the opportunity to choose a career and an environment arranged to facilitate the occupation.…”
Section: Creation Of Job Opportunities For Older Adultsmentioning
confidence: 99%
“…This study also responds to the Australian "National Arts and Health Framework" which was endorsed by both Health Ministers and Arts Ministers in every Australian state/territory to promote the integration of the arts into health policy and practice (16), and the recent Australian Royal Commission into aged care that found that many older Australians are isolated, lonely and lack the intellectual activity/resources needed to live a meaningful life (6, 17). Arts interventions and programs for older adults have been found to reduce depressed mood, social isolation, boredom; enhance feelings of joy, happiness, hope, selfworth, relaxation and improve quality of life (14,(18)(19)(20)(21)(22)(23). In the general population, qualitative and quantitative studies have found that arts engagement increases perceptions of happiness, resilience, empathy, enjoyment, confidence, self-esteem, self-expression, knowledge, and self-reflection (8,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%